A balance between circular and linear forms of the dengue virus genome is crucial for viral replication - Villordo, Sergio (2010)
The plasticity of viral plus strand RNA genomes is fundamental for the multiple functions of these molecules. Local and long-range RNA - RNA interactions provide the scaffold for interacting proteins of the translation, replication, and encapsidation machinery. Using dengue virus as a model, we investigated the relevance of the interplay between two alternative conformations of the viral genome during replication. Flaviviruses require long-range RNA - RNA interactions and genome cyclization for RNA synthesis. Here, we define a sequence present in the viral 3′UTR that overlaps two mutually exclusive structures. This sequence can form an extended duplex by long-range 5′-3′ interactions in the circular conformation of the RNA or fold locally into a small hairpin (sHP) in the linear form of the genome. A mutational analysis of the sHP structure revealed an absolute requirement of this element for viral viability, suggesting the need of a linear conformation of the genome. Viral RNA replication showed high vulnerability to changes that alter the balance between circular and linear forms of the RNA. Mutations that shift the equilibrium toward the circular or the linear conformation of the genome spontaneously revert to sequences with different mutations that tend to restore the relative stability of the two competing structures. We propose a model in which the viral genome exists in at least two alternative conformations and the balance between these two states is critical for infectivity.